2018
DOI: 10.1155/2018/1731459
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer Activity and Potential Mechanism of Action of the Leaves of Spondias mombin L.

Abstract: Spondias mombin L. is used in folk medicine for the treatment of inflammation and gastrointestinal diseases. Our study investigated the antiulcer activity of S. mombin ethanolic extract (SmEE) and its majority compounds gallic acid (GA) and ellagic acid (EA). Phytochemical characterization was performed by HPLC. The SmEE was screened for in vitro antioxidant activities using phosphomolybdenum, ABTS, DPPH, and FRAP assays. The antiulcer activity of SmEE, GA, EA, or GA + EA was evaluated by gastric lesion models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 98 publications
2
27
0
2
Order By: Relevance
“…Both PGE 2 and TNF-α can be controlled by TLR-2/ MyD88 signaling pathway, and numerous studies have demonstrated that downregulation of TLR-2/MyD88 signaling pathway [37], promotion of PGE 2 secretion [4], and inhibition of TNF-α expression [3,5] could make important contribution to the suppression of the development of peptic ulcer. In the present study, we observed the marked upregulation of TLR-2, MyD88, and TNF-α in the epithelium and the granulation tissues at the base of the ulcer, compared with normal duodenal tissues without ulcers, which implied that these factors could accelerate ulcer formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both PGE 2 and TNF-α can be controlled by TLR-2/ MyD88 signaling pathway, and numerous studies have demonstrated that downregulation of TLR-2/MyD88 signaling pathway [37], promotion of PGE 2 secretion [4], and inhibition of TNF-α expression [3,5] could make important contribution to the suppression of the development of peptic ulcer. In the present study, we observed the marked upregulation of TLR-2, MyD88, and TNF-α in the epithelium and the granulation tissues at the base of the ulcer, compared with normal duodenal tissues without ulcers, which implied that these factors could accelerate ulcer formation.…”
Section: Discussionmentioning
confidence: 99%
“…e number and the severity of discrete areas of gross damage in the mucosa were examined under a three-fold magnifier and assessed by two pathologists who were unaware of the drug treatment. e ulcer score of the rat duodenum was graded on a 0-5 point scale based on the severity of erosion and formation of hemorrhages according to the modified method described by Cantarella et al [20] as follows: almost normal, no damage (0), pinpoint erosions (1), lesions < 1 mm length (2), lesions 1-2 mm length (3), lesions 3-4 mm length (4), and lesions > 4 mm length (5). e ulcer score for each rat was calculated as the number of lesions multiplied by their corresponding score.…”
Section: Evaluation Of Duodenal Mucosal Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments for this study and a related study were carried out jointly so that for the control and ranitidine groups, data from the same animals is used for both this study and a previously published study [9], allowing a reduction of 12 animals.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, they found that the major compounds found in SmEE, ellagic acid and gallic acid are gastric protectors and when evaluated in association the protective activity is increased [9]. …”
Section: Introductionmentioning
confidence: 99%